Transgender Adaptation Strategies to Community Social Construction in Padang City - Lenggogeni, Putri; Indrawadi, Junaidi (Science and Environmental Journal for Postgraduate, 2021)
This research is a study of transgender people who carry out adaptation strategies to the social construction of society in Padang City, by taking a case study in the West Padang location. This study describes a transgender adaptation strategy that aims to 1) analyze the meaning of transgender people on their gender identity; 2) analyze the social construction of the community towards transgender and 3) analyze the transgender strategy in adapting to the social construction of the community. Withdrawal of informants is done by purposive sampling. The method used by the author is descriptive qualitative. Data collection techniques used are observation, interviews, and documentation. The results showed that 1) the meaning of transgender women for their gender identity: a) as a woman; b) wanting to look beautiful in the eyes of the community; and c) not hiding as a transvestite. So the meaning for transgender is as a choice because they want to be recognized for their existence, there is a sexual desire if they become a woman, inner satisfaction, and pleasure in themselves; 2) gender social construction of transgender people is seen from: a) as people who have deviant behavior; b) violating values and norms; c) amused, uncomfortable, uncomfortable with transgender; d) fear of the impact of transgender on normal children, e) labeling transgender. This point concludes that the existence of transgender in the community initially received social pressures that made their mental patience tested, but over time slowly they (transgender) could be accepted well in society; 3) transgender strategies in adapting to the community environment: a) interact well; b) adjust the appearance; c) maintain attitudes and behavior. The strategy of transgender is to be able to interact in the environment by associating and interacting with the community, besides that transgender also respect and uphold the values of maintaining ethics, mutual respect, both among teenagers, children and parents, so that later good relationships will be created.